HER2 expression in breast cancer primary tumours and corresponding metastases. Original data and literature review - Carlsson, J (Nature Publishing Group, 2004)
The aim of this study was to evaluate whether the HER2 expression in breast cancer is retained in metastases. The HER2 expression in primary tumours and the corresponding lymph node metastases were evaluated in parallel samples from 47 patients. The HercepTest was used for immunohistochemical analyses of HER2 overexpression in all cases. CISH/FISH was used for analysis of gene amplification in some cases. HER2 overexpression (HER2-scores 2+ or 3+) was found in 55% of both the primary tumours and of the lymph node metastases. There were only small changes in the HER2-scores; six from 1+ to 0 and one from 3+ to 2+ when the metastases were compared to the corresponding primary tumours. However, there were no cases with drastic changes in HER2 expression between the primary tumours and the corresponding lymph node metastases. The literature was reviewed for similar investigations, and it is concluded that breast cancer lymph node metastases generally overexpress HER2 to the same extent as the corresponding primary tumours. This also seems to be the case when distant metastases are considered. It has been noted that not all patients with HER2 overexpression respond to HER2-targeted Trastuzumab treatment. The stability in HER2 expression is encouraging for efforts to develop complementary forms of therapy, for example, therapy with radionuclide-labelled Trastuzumab.